2018
DOI: 10.1002/jbt.22263
|View full text |Cite|
|
Sign up to set email alerts
|

Naringin prevents ultraviolet‐B radiation‐induced oxidative damage and inflammation through activation of peroxisome proliferator‐activated receptor γ in mouse embryonic fibroblast (NIH‐3T3) cells

Abstract: The present study, we investigate the preventive role of naringin, a dietary flavonoid, against ultraviolet‐B (UVB) radiation (280‐320 nm) induced oxidative damage and inflammatory responses in mouse embryonic fibroblast cell lines (NIH‐3T3). In this study, 20 mJ/cm 2 of UVB radiation induces cell cytotoxicity, reactive oxygen species (ROS) generation, DNA damage, and antioxidants depletion in NIH‐3T3 cells. Treatment with naringin (60 µM) prior UVB exposure prevented the cell cytotoxicity, ROS generation, DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 62 publications
0
6
0
1
Order By: Relevance
“…The color transition from purple to yellow was read at 517 nm spectrophotometrically. The color transition depended on the quantity and quality of the sample used ( NilamberLal Das et al, 2019 ). The hydroxyl (OH – ) scavenging was evaluated by the Ansar et al ( Ansar et al, 2020 ) process.…”
Section: Methodsmentioning
confidence: 99%
“…The color transition from purple to yellow was read at 517 nm spectrophotometrically. The color transition depended on the quantity and quality of the sample used ( NilamberLal Das et al, 2019 ). The hydroxyl (OH – ) scavenging was evaluated by the Ansar et al ( Ansar et al, 2020 ) process.…”
Section: Methodsmentioning
confidence: 99%
“…The sunscreen effect of natural materials is essential for antiphotoaging material development. Several phytochemicals such as caffeic acid [ 28 ] and naringin [ 29 ], isolated from natural resources, have been reported to have sunscreen properties. Notably, we observed that the SPF value of WEAOR was 3.43, which is a remarkable value compared with that of para-aminobenzoic acid (13.86).…”
Section: Resultsmentioning
confidence: 99%
“…The chemiluminescence (ECL) method was then used to develop blots. Further, Image J software quantified the blotting band image strength 38 …”
Section: Methodsmentioning
confidence: 99%